Training for the Elderly to Improve Skills in Preventing and Managing Chronic Diseases - Yuke Andriane; Santun Bhekti Rahimah; Miranti Kania Dewi; Siti Annisa Devi Trusda; Fajar Awaliya Yulianto (International Journal Of Community Service, 2024)
An increasing elderly population in the world has a broad impact on society. Elderly people have different characteristics and are vulnerable to physical and psychological health problems, one of which is chronic diseases such as hypertension, diabetes, and coronary heart disease. The elderly require special attention from their families, surrounding communities, and the local government. In response to this, the Unisba Faculty of Medicine organized a Community Service (PKM) activity called "Training for the Elderly to Improve Skills in Preventing and Managing of Chronic Diseases." This activity aims to enhance the knowledge and skills of the elderly in preventing and managing their diseases, which will help prevent complications and increase the quality of life of the elderly. This, in turn, will empower them to remain productive members of society. PKM activities occurred in Cihanjuang Village on July 22-23, 2022. The event was a collaboration of Unisba Medical Faculty, the Cihanjuang village government, and the Parongpong District. A PKM activity was conducted offline for two days with around 60 participants. The activity included comprehensive health education material, assistance and mentoring for elderly people in sports activities, examination and modification of risk factors for chronic diseases. Detection of disease through checking blood pressure, independent blood sugar monitoring at home, and anthropometric examination including body weight, height, upper arm circumference, and waist circumference. The result of these activity showed that the knowledge of elderly on chronic disease management increased by 19.79% based on analysis of pre-test and post-test. It also enhanced the skills of elderly people in early detection and modification of risk factors for chronic diseases. The measurement results indicate that 11.32% of participants are at risk based on BMI, 54,72% are classified as obese 1, and 33.96% are classified as obese 2. All of the participants had a risk of comorbidities based on BMI and waist circumference calculations, with some falling into the category of increased 9.43%, moderate 3.77%, severe 52.83%, and very severe 33.96%. This program will support the accelerated development of Active Alert Villages and Subdistricts as one of the performance targets in the community empowerment process to improve the community's welfare. Keywords: Elderly, chronic disease, co-morbidities, knowledge, skills, Cihanjuang